Sadar pilah sampah dengan konsep 4R (Reuse, Reduce, Recycle, Replace) dalam upaya penurunan volume sampah Desa Pantai Gemi tahun 2022 - Putri, Syafreni Annisa Ayu; Santi, Devi Nuraini; Indirawati, Sri Malem; Naria, Evi (TROPHICO: Tropical Public Health J., 2023)
Diseases can be spread directly or indirectly via unprocessed garbage. Garbage management is crucial if we want to reduce the negative effects that waste has on our health. The community of Pantai Gemi lacks waste-processing infrastructure. The Sanitation Service's inaccessible trash transportation system, which forces people to process waste on their own, is the root of this issue. One significant effort that can be made is to educate the community. This study sought to ascertain how public perception has changed as well as how much less inorganic and organic trash was being produced as a result of the extension intervention. A pre-test-post-test design with one group is used in this kind of research. All of the 2,179 family heads who make up the study's population make up its sample of 30 families. Seven respondents, according to data on changes in respondents' knowledge, report changes in their knowledge of waste management. The results of the normality test demonstrate the homogeneity of the waste generation statistics. The Dependent Sample T-Test method was used to examine waste generation. The analysis of the volume of inorganic waste yielded t = 0.00<0.05, indicating that intervention has an effect on decreasing the volume of inorganic waste in Pantai Gemi Village. The analysis of the weight loss of organic waste yielded t = 0.00<0.05, indicating that intervention has an effect on weight loss of organic waste in Pantai Gemi Village. Residents of Pantai Gemi Village should be given advice by the Department of Cleanliness and the Environment. For the Gemi Beach Village Apparatus to be able to connect the neighborhood's trash management efforts with relevant organizations. For Pantai Gemi Village inhabitants to become accustomed to and learn more about handling waste on their own.